Islam and Jihad: the Quest for Peace and Tolerance - Syamsul Rijal (Universitas Islam Negeri Alauddin Makassar, 2015)
The topic of the writing is Islam and Jihad. The main focuses of this writing is how the concept of “Jihad” understood by the West, which is labeled as “Radical Islamist” on the base of the action of the radical Islamic groups, while Islam undermines tolerance and peace? The methodology of this writing is descriptive analyzes of the concept of Islam and jihad. It found that the idea of jihad has multiple meanings in Islam which is not confined to holy war. It is lesser jihad which is considered as holy war. However, holy war in Islam does not refer to military aggression as understood within the Christian tradition. The values of peace and tolerance are emphasized as Islam is very concerned with the sanctity of human life, justice and humanity. In addition, the history of Islam has shown that in the classical era Muslims could coexist with non-Muslims in harmony and peace. It is clear that Islam is deeply concerned with peace and tolerance such as Silm, assalamu alaikum etc. Jihad has been misunderstood and distorted in the west and among Muslim radicals as it tends to be associated with Muslim aggression, holy war, violence, and terrorism.